2004
DOI: 10.1080/09540120412331292462
|View full text |Cite
|
Sign up to set email alerts
|

Talking about STD/HIV prevention: a look at communication online

Abstract: Little is known about the quality and usability of online health information. This analysis evaluated STD prevention websites' content quality and usability. Thirty-six sites were analyzed to determine their adherence to established sexual health guidelines and their accessibility, usability, credibility and currency. The objective of this study was to determine what communication skills are available to teenagers through STD prevention websites. Only two (6%) addressed safe sex negotiation; seven (19%) addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…For example, a substantial part of the research concerning HIV and STIs and sexually related uses of the Internet has focused on gay men who meet offline sex partners online (e.g., Bolding, Davis, Hart, Sherr, & Elford, 2005;Bowen, Williams, & Horvath, 2004;Bull, McFarlane, Lloyd, & Rietmeijer, 2004;Elford, Bolding, & Sherr, 2001;Hospers, Kok, Harterink, & de Zwart, 2005;McFarlane, Ross, & Elford, 2004;Tikkanen & Ross, 2000. The rationale for conducting these studies has partly been to investigate how the Internet can be used by health professionals for intervention and preventive actions (e.g., Bolding et al, 2005;Hospers, Harterink, Van Den Hoek, & Veenstra, 2002;Kalichman, Benotsch, Weinhardt, Austin, & Luke, 2002;Keller, Labelle, Karimi, & Gupta, 2004;Klausner, Levine, & Kent, 2004;Levine & Klausner, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…For example, a substantial part of the research concerning HIV and STIs and sexually related uses of the Internet has focused on gay men who meet offline sex partners online (e.g., Bolding, Davis, Hart, Sherr, & Elford, 2005;Bowen, Williams, & Horvath, 2004;Bull, McFarlane, Lloyd, & Rietmeijer, 2004;Elford, Bolding, & Sherr, 2001;Hospers, Kok, Harterink, & de Zwart, 2005;McFarlane, Ross, & Elford, 2004;Tikkanen & Ross, 2000. The rationale for conducting these studies has partly been to investigate how the Internet can be used by health professionals for intervention and preventive actions (e.g., Bolding et al, 2005;Hospers, Harterink, Van Den Hoek, & Veenstra, 2002;Kalichman, Benotsch, Weinhardt, Austin, & Luke, 2002;Keller, Labelle, Karimi, & Gupta, 2004;Klausner, Levine, & Kent, 2004;Levine & Klausner, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…In an attempt to address issues of quality, Keller et al 174 used a content analysis approach to assess HIV/STI prevention websites for teenagers. In their study, coding tools were developed and applied to assess communication, information provision and usability (such as currency, authority, readability and objectivity) of the websites.…”
Section: Intervention Designed For Online Use: Keep It Real 111mentioning
confidence: 99%
“…The former concluded that Web sources tend to present more negative or narrow-minded viewpoints, often employing a "sex as victimization" message instead of promoting the positive aspects of sexual exploration. Keller et al (2002Keller et al ( , 2004 similarly found a lack of negotiation messages online, which when present may help young people navigate sexual conflicts. Together, these studies suggest that positive and more user-driven messages may be lacking from online sex education resources.…”
Section: Quality Assessment Of Adolescent-targeted Online Sex Informamentioning
confidence: 87%